WEBQUESTS AS A METHOD OF COLLABORATIVE TEACHING - Shaukenova, Nazu (European Scientific Journal, ESJ, 2015)
The question of information and communication technologies (ICTs) utilization is very broad and in recent years has attracted several studies especially how it relates to discourses on teaching in higher institutions of learning. Apart from making it possible for students to gain knowledge better, ICTs have proved its relevance for teaching processes too. Through various studies conducted globally, findings show that the level of integration of ICTs in teaching has reached an appreciable level.